Risk factors of mild behavioral impairment: a systematic review - Tang, Song Lin; Subramaniam, Ponnusamy; Siau, Ching Sin; Chong, Agnes Shu Sze; Liu, Fang (Frontiers in Psychology, 2025)
IntroductionMild Behavioral Impairment (MBI) represents a predementia syndrome marked by neuropsychiatric symptoms that may precede detectable cognitive decline. Identifying factors associated with MBI is critical for developing targeted prevention strategies in neurodegenerative disorders.MethodsThis systematic review adhered to PRISMA 2020 guidelines, searching PubMed, Scopus, Web of Science, ScienceDirect, and Embase through May 2024. Forty-one human studies meeting predefined inclusion criteria were selected through dual independent screening.ResultsFive key domains emerged: (1) Genetic susceptibility (APOE ε4 allele showing strongest association), (2) Motor system pathology (particularly Parkinsonian features), (3) Multisensory deficits (auditory impairment demonstrating bidirectional relationships), (4) Metabolic dysregulation (diabetes mellitus and frailty phenotypes), and (5) Neuroanatomical correlates (frontolimbic atrophy patterns on MRI). The interaction between genetic predisposition and environmental/lifestyle factors appears central to MBI pathogenesis.ConclusionMBI manifests as a multidimensional interface between molecular mechanisms and clinical phenomenology. Our synthesis supports the implementation of transdiagnostic screening protocols integrating behavioral biomarkers with conventional cognitive assessments. Future research should prioritize longitudinal designs to establish causal pathways and intervention thresholds.